Comparison of Neoadjuvant Chemotherapy With FLOT and Modified DCF Regimens in Nonmetastatic Gastric Adenocarcinoma - Mehdi Pourghasemian; Maryam Salimi; Effat Iranijam; Mohammad Negaresh (Cancer Reports)
ABSTRACT Backgrounds Gastric adenocarcinoma is a common and severe type of malignancy. Treatment for advanced cases involves neoadjuvant chemotherapy before surgery and adjuvant chemotherapy if needed. Aims In this study, a comparison of two regimens of FLOT and mDCF has been conducted with regard to pathological and radiological response, as well as complications. Methods and Results The medical records of patients diagnosed with nonmetastatic gastric adenocarcinoma who randomly received therapy with either FLOT or mDCF regimens were studied. The two groups were compared regarding complications, radiological response based on RECIST Ver 1.1 criteria, the chance of successful gastrectomy, pathological response based on the TRG scale, and downstaging of the gastric adenocarcinoma following chemotherapy. In total, 90 patients were studied. 40 patients were treated with the mDCF regimen, while 50 received the FLOT regimen. The mDCF group experienced more side effects, and the FLOT group had higher response rates and a greater percentage of patients who underwent surgery with clear margins. Additionally, patients receiving FLOT treatment showed greater lymphatic involvement, tissue invasion, and disease stage improvement. Conclusion According to the study, patients with limited local invasion gastric adenocarcinoma who are eligible for surgery may benefit more from the FLOT neoadjuvant regimen than the mDCF regimen. The FLOT regimen proves to be more efficient and has fewer complications.